Study the Mechanical Properties of (Al-Cu-Mg) Matrix Composites Reinforced by Alumina Particles - Abdullah M. Ali (Tikrit Journal of Pure Science)
The aim of the present research is studying the mechanical properties of composites matrix fabricated of aluminum (Al-4.5%Cu-1.5%Mg) by cast and to proceeding the heat treatment solution from different temperatures 500oC, 525oC and 550oC for different times 2hr and 4hr, and then proceeding the requil hardness (HBR), Therefore we conducted the optimum value from the alloy basic (A) at the temperature 550oC for 6hr time.